2021
DOI: 10.3390/ijerph18168719
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia in Trauma

Abstract: Hypothermia in trauma patients is a common condition. It is aggravated by traumatic hemorrhage, which leads to hypovolemic shock. This hypovolemic shock results in a lethal triad of hypothermia, coagulopathy, and acidosis, leading to ongoing bleeding. Additionally, hypothermia in trauma patients can deepen through environmental exposure on the scene or during transport and medical procedures such as infusions and airway management. This vicious circle has a detrimental effect on the outcome of major trauma pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…As tissue oxygen consumption is limited by shock, hypothermia is further exacerbated by insufficient heat production. Early hypothermia increases the cardiac output and oxygen consumption, while later hypothermia can inhibit myocardial contractility and decrease the cardiac output [ 6 ]. It demonstrated that shock can trigger hypothermia and that spontaneous hypothermia due to hypothermic exposure can exacerbate hemorrhagic shock [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As tissue oxygen consumption is limited by shock, hypothermia is further exacerbated by insufficient heat production. Early hypothermia increases the cardiac output and oxygen consumption, while later hypothermia can inhibit myocardial contractility and decrease the cardiac output [ 6 ]. It demonstrated that shock can trigger hypothermia and that spontaneous hypothermia due to hypothermic exposure can exacerbate hemorrhagic shock [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While numerous experimental studies in animal models reported promising results (e.g., a decrease in TNF-α release and a delay in IL-1 and IL-6 release, increased concentrations of interleukin-10, and increased survival after hemorrhagic shock were shown after intervention with hypothermia) [46,48,49], the mechanisms by which hypothermia influences the posttraumatic immune response after multiple trauma proofed difficult to unravel. Additionally, hypothermia can affect trauma-induced coagulopathy by impaired clotting factor activity and platelet function [50][51][52]. However, data from a study of 310 multiple-trauma patients found that accidental hypothermia was not an independent risk factor for post-traumatic complications (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…In the Ukraine war, for example, cold exposure is a relevant medical problem causing cold injuries [ 4 ]. It is well documented that hypothermia worsens coagulation and deteriorates traumatic bleeding [ 5 ]. To our knowledge, no systematic review data exists on preventable causes of traumatic death in cold climates.…”
Section: Introductionmentioning
confidence: 99%